PENERAPAN VIDEO TUTORIAL PEMBUATAN BATIK TEKNIK CAP PADA ELEMEN EKSPERIMEN TEKSTIL DI FASE F SMKN 1 JATIREJO - Sindy Dwi Mardianti; Mita Yuniati (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to 1) describe the feasibility of a video tutorial on making batik using the stamp technique (cap), 2) describe students' batik-making skills after the implementation of the video tutorial on stamp technique batik at SMKN 1 Jatirejo, and 3) describe the responses of Fashion Design students at SMKN 1 Jatirejo to the implementation of the video tutorial. This study employed a quantitative descriptive approach with a pre-experimental one-shot case study design. The research subjects consisted of 34 students from class XI DPB 2 at SMKN 1 Jatirejo. The data collection instruments used included: 1) a video tutorial validity assessment sheet by three media experts and three material experts, 2) a psychomotor skills assessment sheet, and 3) a student response questionnaire. The results of this study indicate that: 1) the validity level of the video tutorial obtained a score of 3.89, categorized as Very Feasible, 2) students' batik-making skills achieved an average of 84.56%, categorized as Very Good, with a classical mastery rate of 97%, and 3) student responses to the use of the video tutorial obtained an average percentage of 83.36%, categorized as Very Positive, indicating that the video helped students understand the procedures for making stamp batik, increased learning motivation, and facilitated practical implementation.